Determinants of credit risks in Islamic banks in Malaysia - 'Azraa Arrmyza, Razif (2015)
The concept of risk was well known to most of us. It has become an important tool in making decision when it is possible to measure it and to assign values to different situations. However the changes in the global finance environment has make Islamic banking institutions are more vulnerable to risks. Many theoretical studies on Islamic banking were conducted with the focus on Islamic modes of financing and their ability to perform financial intermediation for catering to the needs of people. This paper examines the determinants of credit risk in Islamic banks in Malaysia. The study uses secondary data obtained from the annual report of selected Islamic banks during the period from 2008 to 2013. Al the selected banks were local Islamic banks in Malaysia. This study uses non-performing financing (NPFs) as a proxy for credit risk which is dependent variable. The independent variables consists of three macroeconomic variables Gross Domestic Product (GDP), Base Financing Rate (BFR) and Consumer Price Indicator (CPI). There are also six other variables (bank specific) that are used as internal variables. These are Bai’ Bithaman Ajil (BBA), Murabahah, al-Ijarah Thumma al-Bai’ (AITAB), total assets, other contract (OCONT) and Profit Margin (PM). In this study it has been found that GDP is significant and negatively related to credit risk, making the finding similar with past studies.